OXER1 and RACK1-associated pathway: a promising drug target for breast cancer progression - Masi, Mirco (Oncogenesis, 2020)
Recent data indicate that receptor for activated C kinase 1 (RACK1) is a putative prognostic marker and drug target in breast cancer (BC). High RACK1 expression is negatively associated with overall survival, as it seems to promote BC progression. In tumors, RACK1 expression is controlled by a complex balance between glucocorticoids and androgens. Given the fact that androgens and androgenic derivatives can inhibit BC cell proliferation and migration, the role of androgen signaling in regulating RACK1 transcription in mammary tumors is of pivotal interest. Here, we provide evidence that nandrolone (19-nortosterone) inhibits BC cell proliferation and migration by antagonizing the PI3K/Akt/NF-κB signaling pathway, which eventually results in RACK1 downregulation. We also show that nandrolone impairs the PI3K/Akt/NF-κB signaling pathway and decreases RACK1 expression via binding to the membrane-bound receptor, oxoeicosanoid receptor 1 (OXER1). High levels of OXER1 are observed in several BC cell lines and correlate with RACK1 expression and poor prognosis. Our data provide evidence on the role played by the OXER1-dependent intracellular pathway in BC progression and shed light on the mechanisms underlying membrane-dependent androgen effects on RACK1 regulation. Besides the mechanistic relevance, the results of the study are of interest from a translational prospective. In fact, they identify a new and actionable pathway to be used for the design of innovative and rational therapeutic strategies in the context of the personalized treatment of BC. In addition, they draw attention on nandrolone-based compounds that lack hormonal activity as potential anti-tumor agents.